Synthesis, characterization and testing of zeolite and alumina supported organometallic (Ni, Pd, Pt and Mo) catalyst for the hydrodeoxgenation of oleic acid and stearic acid into N- and iso-paraffin biofuel / Ayodele Olumide Bolarinwa - Ayodele Olumide, Bolarinwa (2015)
This report provides additional knowledge to bridge the existing gap in the surveyed literature in the aspect of organometallic catalyst synthesis for the hydrodeoxygenation (HDO) and isomerization (ISO) of biomass into high grade biofuel. Prior to catalyst synthesis, a thermodynamic feasibility study was carried out using Aspen Hysys Process Simulator v7.2 to establish the feasibility of HDO reaction of oleic acid (OA). Subsequently, in order to validate the germane ability of organometallic catalyst in HDO process, two Ni supported catalyst were synthesized and tested on the HDO of OA. The first nickel alumina catalyst (Ni/Al2O3) was synthesized via the incorporation of inorganic Ni precursor into Al2O3, while the second (NiOx/Al2O3) was via the incorporation nickel oxalate (NiOx) prepared by functionalization of Ni with oxalic acid (OxA) into Al2O3. Their characterization results showed that Ni species present in Ni/Al2O3 was 8.2% while 9.3% was observed for NiOx/Al2O3 according to the energy dispersive X-ray (EDX) result. Consequently, NiOx/Al2O3 has a better HDO activity producing 63% n-C18H38 compared to 41% n-C18H38 produced by Ni/Al2O3. In addition, NiOx/Al2O3 produces 16% iso-C18H38 which is considered biofuel-essential-component. The superiority of NiOx/Al2O3 was ascribed to the OxA functionalization which also increases its acidity and guarantee high Ni dispersion as seen in the X-ray diffraction (XRD) result. In view of this, other synthesized catalysts were functionalized with OxA. Furthermore, two Pd functionalized with OxA and supported on zeolite (PdOx/Zeol) catalysts were synthesized and one was further modified with fluoride ion (FPdOx/Zeol) to enhance its acidity. Their HDO activities results did not show clear distinction, however, FPdOx/Zeol has higher ISO activities producing 24.8% iso-C18H38 compared to 16% produced by PdOx/Zeol. Consequently Mo, Pt and Ni–Mo were equally functionalized as FMoOx/Zeol, FPtOx/Zeol and NiMoFOx/Zeol, respectively, characterized and tested on HDO of OA. Their scanning electron microscopy (SEM) and XRD characterization results showed that all the catalysts loss varying degree of crystallinity which resulted into increase in their Si/Al ratio due to the effect of OxA/fluoride ion functionalization and calcination which removes the extra framework alumina and framework alumina, respectively. The effect of crystallinity loss was of the order FMoOx/Zeol > FPdOx/Zeol > FPtOx/Zeol > NiMo/FOxZeol > PdOx/Zeol > NiOx/Al2O3. The study on the effect of operational variables showed that temperature, pressure, time, catalyst loading and gas flowrate have strong influence on the process. In the optimization study using FPtOx/Zeol, the optimum conditions for the HDO and ISO of OA were 58 min reaction time, 27.8 mg FPtOx/Zeol loading, 18 bar and 364 °C to produce 28.39% iso-C18H38 and 68.93% n-C18H38. A study on the comparison of the economic and technical viability of the organometallic catalysts based on cost of the catalysts precursor with respect to their observed HDO and ISO abilities showed that the catalysts cost effectiveness was of the order NiMoFOx/Zeol, NiOx/Al2O3, FMoOx/Zeol, FPdOx/Zeol, PdOx/Zeol and FPtOx/Zeol. In addition, during the reusability results, NiMoFOx/Zeol also showed superiority to others strictly owing to its preparation procedure that first employed Mo to modify the Zeol support prior to Ni precursor incorporation.